A qualitative study of green human resource management practices and challenges in Bangladesh’s leather sector - Hossain, Mafruha; Islam, Mohammad Thoufiqul; Alam, Md. Kausar (International Journal of Management and Sustainability, 2026)
Over the past decades, the pressures toward environmental sustainability have increased worldwide. Green Human Resource Management (GHRM) is a new green practice necessary for developing a corporate culture of environmental responsiveness. However, there are challenges in implementing GHRM. This paper aims to define the GHRM practices used in the leather goods industry in Bangladesh and identify perceived impediments to their implementation, addressing the lack of research on GHRM in the Bangladesh context. Eight semi-structured interviews were conducted using the Key Informant Interview (KII) technique with human resource managers from leather goods and footwear companies. The data obtained were analyzed through thematic analysis to identify key themes. The findings indicate that companies manufacturing leather products are making efforts to adopt GHRM practices, yet they face several challenges, such as bureaucratic issues, budget deficiencies, and the absence of green knowledge management within the companies. These findings can be valuable to policymakers and regulatory organizations, helping facilitate the adoption of green HR practices by industry players by addressing these obstacles. By applying the Resource-Based View, the study emphasizes the importance of formulating policies and frameworks that enable strategic resource use to overcome barriers to GHRM. Such measures will support environmental sustainability and promote growth in the leather goods and footwear industry in Bangladesh.